The Effect of Carbon Emission Disclosure, Corporate Social Responsibility Disclosure, and Eco-efficiency on Firm Value - Fitri, Alya Noviana; Putra, Vicky Dzaky Cahaya (E-Jurnal Akuntansi, 2025)
Economic growth in recent years has shown rapid improvement in the industrial sector. This progress has given rise to various environmental problems, including increased carbon emissions and global warming due to industrial activities. The purpose of this study is to examine and analyze the effect of Carbon emission disclosure, CSR Disclosure, and Eco-efficiency on Firm Value. The sample for this study was selected using purposive sampling, resulting in 19 companies in the Basic Materials Manufacturing Sub-Sector during the 2021-2024 period with a total of 76 data points. The data analysis technique used multiple linear regression. The results show that Carbon emission disclosure and CSR Disclosure do not affect firm value. Meanwhile, Eco-efficiency has a significant positive effect on firm value.